Marketplace for buying and selling the agricultural products and vegetables - Hamza, mammadi; hamied, abd el djalale (university of eloued جامعة الوادي, 2022)
Malgr´e le d´eveloppement remarquable dans le monde, l’Alg´erie souffre encore du manque d’exploitation des technologies telles que les applications (logiciels). Nous nous concentrerons sur cette th`ese sur le type sp´ecifique d’applications li´ees au commerce ´electronique dans le domaine agricole. A travers ce travail, nous d´evelopperons une application mobile r´esolvant les probl`emes des clients et des agriculteurs dons l’Alg´erie comme : Instabilit´e des prix, Monopole. . . .Et cette application assurera : des alternatives aux clients, l’acc´el´eration des ´echanges....Despite the remarkable development in the world, Algeria still suffer from the lack of exploitation of technology such as applications(Softwares). We will focus on this thesis about specific type of applications related to electronic commerce in the agricultural field. Through this work, we will develop a mobile application solve problems of client and farmers around the Algeria like : Price instability, Monopoly. . . .And this application ensure : alternatives to customers, accelerating trade ....
licence mémoire informatique
Keywords: E-commerce, application mobile, boutique en ligne, ´elevage, agriculture.; E-commerce, mobile application ,online store ,farming, agriculture.